Causal association of gastroesophageal reflux disease on irritable bowel syndrome: a two-sample Mendelian randomization study - Wu, Huihuan; Li, Jingwei; Li, FeiFei; Lun, Weijian (Frontiers in Genetics, 2024)
Background: Recently observational studies have reported that gastroesophageal reflux disease (GERD) is commonly associated with irritable bowel syndrome (IBS), but the causal relationship is unclear.Methods: We conducted a two sample Mendelian randomization study utilizing summary data from genome wide association studies (GWASs) to explore a causal relationship between GERD (N cases =129,080) and IBS (N cases=4,605) of European ancestry. Furthermore, the inverse-variance weighted method and a series of sensitivity analyses were used to assess our results accuracy and confidence.Results: We found a significant association of GERD on IBS (NSNP=74; OR:1.375; 95%CI: 1.164-1.624; P<0.001). Reverse analysis showed no evidence of a causal association for IBS on GERD (NSNP=6; OR:0.996; 95%CI:0.960-1.034; P=0.845).This study provides evidence that the presence of GERD increases the risk of developing IBS, and the reverse MR results observed that IBS did not increase the risk of GERD.